Best Practice Implementasi Sistem Penilaian Terpadu Sistem Penilaian Mandiri Dalam Jaringan di SMK Negeri 1 Kalijambe - Hasan, Hasanudin Dwi Sabdo Putro (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study is to (1) find out the implementation of Si Pandu, (2) find out the results and impacts achieved after the implementation of the use of Si Pandu, (3) identify the obstacles that occur in the implementation of Si Pandu (4) describe the factors that support the implementation of Si Pandu in monitoring self-assessment in the network at SMK Negeri 1 Kalijambe. This scientific publication is the best experience in carrying out official duties in monitoring and supervising the implementation of online learning assessments. In conclusion, the implementation of Si Pandu in monitoring the participation of self-assessment in the network is carried out quite systematically so as to provide convenience to students, teachers, homeroom teachers and all relevant stakeholders. After using Si Pandu, results were obtained where the evaluation monitoring process was more effective and efficient, thus making it easier for stakeholders to get sufficient information about the progress of the assessment implementation. Constraints that occur in the implementation of Si Pandu in monitoring the assessment process can be anticipated since making the application so that instructions for the solution have been prepared. The implementation of Si Pandu in monitoring self-assessment in the network is supported by adequate factors, both physical and non-physical, internal and external.